Characterization of biochar produced from paperboard sludge: A sustainable approach for waste management and resource recovery - Vaishnavi, P; Sherene, J R T; Baskar, M; Vanniarajan, C; Ramjani, S A; Senthil, K; Selvamurugan, M (Plant Science Today, 2025)
The pulp and paperboard industry are a significant industrial sector that consumes large quantities of fresh water and generates substantial volumes of wastewater. Treating this wastewater produces a considerable amount of sludge, which poses serious environmental challenges. This study proposes a sustainable solution by converting paperboard sludge (PBS) into biochar through slow pyrolysis at temperatures ≤500°C, offering an alternative approach to waste management and resource conservation. The physicochemical analysis of paperboard sludge biochar (PBSB) revealed a neutral pH of 7.49, EC (electrical conductivity) of 0.09 dS m-1, an OC (organic carbon) content of 38.12% and a calcium carbonate (CaCO3) content of 24.5%. Proximate analysis of PBSB revealed an increased fixed carbon content of 10.27 %, total organic carbon (TOC) of 7.13% and reduced volatile matter and moisture levels. Micronutrients viz., iron (Fe) (5.06 mg L-1), manganese (Mn) (419.3 mg L-1), copper (Cu) (26.3 mg L-1) and zinc (Zn) (66.1 mg L-1), were also observed in PBSB. Fourier Transform Infrared Spectroscopy (FTIR) analysis identified various carbon-containing functional groups, including C-Cl, C-N, C-C, H-C=O, C-H and -C≡C-H, indicating substantial chemical transformations during pyrolysis. Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) analysis revealed that PBSB consists of fine particles with a coarse, fluffy, spongy, porous structure, making it ideal for water adsorption. Elemental analysis through x-ray diffraction (XRD) showed high carbon and oxygen content and significant amounts of aluminosilicates, carbonates and nutrients like phosphorus (P) and potassium (K), suggesting PBSB as a potential slow-release fertilizer. This research highlights the potential of biochar derived from paperboard waste as a sustainable solution for effective waste management and resource recovery.